ANALISIS MANAJEMEN DENGAN PENDEKATAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) DESA DI BADAN USAHA MILIK DESA (BUMDES) - Rao, Don Gusti (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study analyzes managerial governance in Village Owned Enterprises (BUMDes) Sukamanah, Bogor Regency with the Village Sustainable Development Goals (SDGs) approach. As an organizational profit, BUMDes Sukamanah has succeeded in generating large profits with superior business units that have economic value, as well as involving local residents collectively, such as village market businesses, provision of clean water facilities, and motor vehicle tax services that are relevant to the SDGs Desa concept, namely the village. proper clean water and sanitation, and equitable economic growth. This descriptive qualitative research method aims to determine the managerial of BUMDes Sukamanah with the SDGs Desa approach. The results showed that the type of business planning, organizing, actuating and controlling the Sukamanah BUMDes was going well in accordance with several points of the SDGs Desa substance. The conclusion of the research is that managerially carried out well in profit organizations with the SDGs Desa approach, generates profits, it is not surprising that Sukamanah BUMDes was awarded as the best BUMDes and became a pilot village with billions of Rupiah assets.